Chowder. Vol 1 [videorecording (DVD)] (Warner Home Video, 2008)
In the colorful town of Marzipan City, the Mung Daal Catering Company cooks up the strangest food you've ever seen. And that's where you'll find Chowder, an adorable apprentice with a big appetite for stirring up trouble!